Plurinational State of Bolivia : Agriculture Public Expenditure Review - World Bank (World Bank, Washington, DC, 2013)
Agriculture is one of the most important sectors for reducing poverty, improving food security, and contributing to the development of Bolivia. There is a need for re-organization and re-prioritization of spending within the sector before an argument for more resources can be made. Recommendations include allocating more resources towards agricultural public goods (such as research and extension among others) to improve sectoral performance and to support a heterogeneous agricultural sector in the context of rapid technological change, climate pressures and food price volatility. There is a need for resource allocations towards research and extension, adherence to the types of production systems in the country. Improving the balance between current and capital expenditures in agriculture is imperative. Within the current component of sectoral expenditures, more money should be spent on human capital. Prioritization and targeting of public agricultural investments is a good starting point for improving sector performance. This prioritization within the agricultural sector should consider the diversity of production systems and agricultural economic units in rural areas. Bolivia needs a coordinated monitoring and evaluation system that enables the tracking of results of the sector as a whole and facilitates the planning of investments. Strong recommendations are made to ensure better implementation of available resources in agriculture.